Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah Terhadap Komitmen Organisasi Guru Pada Sekolah Lanjutan Tingkat Atas (SLTA) Negeri Dan Swasta Di Kota Tanjungpinang, Provinsi Kepulauan Riau - Mey Krisselni Sitompul (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
ABSTRACT This study aims to determine the effect of headmaster’s transformational leadership style on the commitment of teacher organizational working in Public and Private Senior High School (SLTA) in Tanjungpinang City. The style of leadership being discussed is the influence idealization, inspiration, motivation, intellectual stimulation, and individual considerations. The sample used is 224 Public and Private Senior High School Teachers in Tanjungpinang City. This Research was conducted by using multiple linear regression which examined the effect of independent variables on dependent variable by using SPSS version 22 software. The sample used in this research is the teacher of Public and Private Senior High School (SLTA) in Tanjungpinang City. From the result, the study found that the variables influence idealization, inspiration, motivation, intellectual stimulation, and individual considerations have a significant effect on teacher organizational commitment. Variable intellectual stimulation has no significant effect on teacher organizational commitment. Simultaneously, the principal leadership style has a significant influence on teacher organizational commitment. Keywords: transformational leadership, influence idealization, inspiration, motivation, intellectual stimulation, individual considerations, and organizational commitment.